The Influence of Knowledge, Awareness and Income on the Interest in Paying Zakat Shares of Investors in North Sumatra - Hamdani, Hamdani; Soemitra, Andri; Harahap, Muhammad Ikhsan (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to identify how knowledge, awareness, and income affect the willingness of investors in North Sumatra to pay zakat on their shareholding. Descriptive quantitative technique was used in this study. A total of 4,333 Islamic equity investors in North Sumatra participated in this study, regardless of whether they have or have not paid zakat on their shares. A total of 98 participants of different ages, all of whom invested in Islamic stocks, were selected as the sample. Information was collected by administering a survey to the participants. SPSS version 25.0 was used to conduct multiple linear regression analysis on the data. The results indicated that the variables of Knowledge, Awareness, and Income Level have a significant positive impact and these three variables simultaneously contribute substantially to an individual's interest in paying zakat on stock ownership, as indicated by the significance value of 0.000 which is very low from the threshold of α = 0.05. The finding emphasizes that the tendency of an individual to pay zakat on shares is influenced by the combination of these three factors, with the contribution of influence reaching 76.7%)